Timothy Asch and ethnographic film - Lewis, E. Douglas, 1947- (Studies in visual culture ;, 2004)
Beautifully illustrated and featuring articles from many of Asch's friends, colleagues, and collaborators as well as an important interview with Asch himself, this is an idea introduction to his work.